Quantum computing - Lwee, Jia Wei (Nanyang Technological University, 2023)
The foundation of quantum computing comes a long way from 1980s to winning the 2022 physics nobel prize. Quantum computing has become a highly popular field of study to research as it tackles computational problems that were deemed impossible to solve. Many large tech companies in the world are investing heavily and angling to stake their place in a quantum future. At present, current technologies has enabled the production of quantum computer, Osprey, a new 433 qubit processor. On the other hand, the quantum computing research have drifted towards software development. In this project, the author examine an approach to apply Hadamard Gate to Fourier Transform and compute the differences between the quantum and classical approach. The author then proposes a quantum algorithm to improve on current sequencing methods called Grover’s search algorithm, which in comparison to classical method, may extract information from an unsorted dataset of size N in a number of iterations on the order of O√N.